Isolation and characterization of novel primary cells from the human distal outflow pathway - Uttio Roy Chowdhury (Nature Portfolio, 2021)
Abstract Ocular hypertension occurs due to increased resistance to aqueous humor removal through the conventional outflow pathway. Unlike the proximal region of the conventional outflow pathway, the distal region has not been well studied, mostly due to lack of model systems. Here we describe isolation and characterization of human primary vascular distal outflow pathway (VDOP) cells from the distal region of the conventional outflow pathway. Tissue from the distal region was isolated from human corneo-scleral rims, digested with collagenase type I (100 U/ml) and placed on gelatin coated plates to allow cellular growth in Dulbecco’s Modified Eagle’s Medium (low glucose) containing fetal bovine serum and antibiotic/antimycotic. VDOP cells showed consistent proliferation for up to 7 passages, retained endothelial-like nature of the parent tissues and showed a unique marker phenotype of Lectin+VEGFR2-CD34-NG2- that was distinct from neighboring trabecular meshwork (Lectin+VEGFR2-CD34-NG2+) and Schlemm’s canal (Lectin+VEGFR2+CD34+NG2+) cells. Dexamethasone treated VDOP cells did not express myocilin and did not form cross-linked actin networks, in contrast to trabecular meshwork cells. These data show that VDOP cells are unique to the distal outflow region and can be used as a viable in vitro model system to understand the biology of the distal outflow pathway and intraocular pressure regulation.